Expanding benzothiadiazole-tetrazole photo-triggered click reaction with chloride ion into reaction-based chloride ion receptor. (July 2021) - Wang, Yashu; Fan, Jingyi; Li, Mengsi; Xie, Xiaojiang; Meng, Xiangru; Ding, Jie; Hou, Hong-Wei
Abstract: There is a great increasing need for effective chloride ion receptors due to the widespread distribution and vital role of chloride ion in nature or industrial production. Up to now, most reported molecule receptors (such as chemosensor) reversibly bind chloride ions via specific intermolecular interactions. Although irreversible binding are achieved by a specifically designed reaction that has advantages in terms of high selectivity and sensitivity, the study of reaction-based molecular receptor for chloride ion is currently unexplored. In this work, we designed and synthesized new BTD-tetrazole compounds to study their photo-triggered click reactions with chloride ions. Interestingly, compounds BT1 and BT2 facilely react with chloride ions under UV light irradiation. In the further exploration for the potential application of reaction-based chloride ion molecular receptor, BT1 or BT2 showed obvious absorption and photoluminescence (PL) responses with good selectivity and sensitivity. Moreover, in the response of BT1 or BT2 to chloride ions, the surprising PL changes induced by the hydrogen bonded aggregate of photochemical product (BHc1 or BHc2 ) provide a new platform to design reaction-based chloride ion receptor. Graphical abstract: In this work, we reported new BTD- tetrazole compounds for the study of photo-triggered click reactions with chloride ion and the potential applications for reaction-based chloride ion receptors. Image 1 Highlights: New BTD- tetrazole compound react with chloride ion under light irradiation. The chloride ion receptor exhibits a dual response with good selectivity. The potential photoreaction-based chloride ion receptor was firstly reported.